Hubungan Antara Self-Esteem Dengan Kecemburuan Pada Dewasa Awal yang Berpacaran - Dewa, Mochamad Refa Mulya; Sarasati, Budi; Viena, Yomima (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to determine the relationship between self-esteem and jealousy in emerging adults who are currently in romantic relationships. The research employed a quantitative approach with a correlational design. The sample consisted of 200 emerging adult respondents in romantic relationships, residing in Bekasi City, selected using a non-probability sampling technique with a quota sampling method. The instruments used in this study were the Multidimensional Jealousy Scale (MJS) and the Self-Liking/Self-Competence Scale-Revised (SLCS-R). The results of the Pearson’s Product Moment correlation test showed a significant negative relationship between self-esteem and jealousy (r = -0.856; p .001). This indicates that the higher an individual’s self-esteem, the lower their level of jealousy in a romantic relationship. Conversely, individuals with lower self-esteem tend to experience higher jealousy. Therefore, the alternative hypothesis (Ha) is accepted. This study highlights the important role of self-esteem in shaping emotional dynamics within romantic relationships.